The Effect of Arithmetic Operations Pockets Media on Improving Concept Understanding and Critical Thinking Skills of Grade 3 Students of SD Negeri 10 Silih Nara - Suwarni Suwarni; Ety Mukhlesi Yeni; Afkar Afkar (FKIP - Universitas Riau, 2026)
This study examines the effect of multiplication pocket media on conceptual understanding and critical thinking skills of third-grade students in elementary school mathematics learning. Mathematics learning at the elementary school level often faces challenges due to the abstract nature of mathematical concepts, particularly multiplication, which is less compatible with students’ cognitive development at the concrete operational stage. This study employed a quantitative approach using a one-group pretest–posttest pre-experimental design involving 30 third-grade students at SD Negeri 10 Silih Nara. Data were collected through validated and reliable essay-based tests designed to measure conceptual understanding and critical thinking skills. The results showed a significant improvement in students’ learning outcomes, with the mean score increasing from 63.00 in the pretest to 87.33 in the posttest. The Wilcoxon Signed-Rank Test indicated a significant difference between pretest and posttest scores (Sig. = 0.000 < 0.05). Furthermore, the N-Gain score of 0.738 was categorized as high, indicating that the multiplication pocket media effectively improves students’ learning outcomes. These findings suggest that the use of concrete and manipulative learning media can enhance students’ conceptual understanding and critical thinking skills in elementary mathematics learning.